Effect of sodium acid phosphate and inosine on the course of Dictyocaulus filaria infection in sheep - Sharma, R L; Batt, T K (The Indian Journal of Animal Sciences, 2012)
A comparative study on effect of sodium acid phosphate (SAP) and inosine (IVO2 releasers) was carried outin Dictyocaulus filaria infected, male Dorset-Muzaffarnagari lambs, aged 8-12 weeks. During patency, SAP andinosine were intravenously administered daily @ 1000 mg/animal, from day-30 post-infection onwards. The comparativeeffect of these drugs on the course of infection was assessed weekly by monitoring alterations in haematobiochemicalparameters and faecal larval output.Animals treated with SAP alone or in combination with inosine had significnatly higher estimated faecal larvaloutput (58.3 and 56.3 million/ animal) during useful patency in comparison with animals receiving inosine (36.2million/animal) and untreated control (24.1 million/animal). Besides, the animals treated with SAP continuedto be in useful patency even at the end of the experiment. In these animals, the post-treatment haematobiochemicalvalues of various parameters restored to near-normal leaves in comparison with infected-untreated controls andor inosine- treated animals. Clinically, these animals had better health status and higher survival rale.